ANALYSIS OF METAPHOR AND SIMILE IN THE POEM AL-I'TIRĀF BY ABU NAWAS - Zikrani Khalilah; Sikni Sari Siagian (Yayasan Haiah Nusratul Islam, 2025)
This paper aims to analyze the influence of the use of metaphors and similes on the aesthetics of Abu Nawas' poetry, especially in the poem entitled